Are some dictators more attractive to foreign investors? - Abel François; Sophie Panel; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
Since political uncertainty is greater in dictatorships than in democracies, we test the hypothesis that foreign investors scrutinize public information on dictators to assess this risk. In particular, we as-sume they use five suitable dictators' characteristics: age, political experience, education level, ed-ucation in economics, and prior experience in business. We perform fixed effects estimations on an unbalanced panel of 100 dictatorial countries from 1973 to 2008 to explain foreign direct investment (FDI) inflows. We find that educated dictators are more attractive to foreign investors. We obtain strong evidence that greater educational attainment of the leader is associated with higher FDI. We also find evidence that the leader having received education in economics and prior experience in business is associated with greater FDI. By contrast, the leader's age, and political experience have no relationship with FDI. Our results are robust to several tests and checks, including a comparison with democracies.
URN:NBN:fi:bof-201907091294
Keywords: F21; F23; 330; foreign direct investment; dictatorships; leader characteristics; political risk